Beobachtungen im Wakhan (NE-Afghanistan) - Mirwald, Peter; Roemer, Hans (ERDKUNDE, 1967)
In summer 1964 the authors conducted a first geological and botanical inventory of Wakhan in Afghanistan. Morphologically, this mountain area is divided into the deeply dissected western Wakhan (2 500 metres), which has the highest peaks (up to 7 000 metres), a transitional middle section and the broader flatter eastern Wakhan (4 000 5 000). The whole valley system shows traces of glaciation. Geologically the mountain range is formed in granite, gneiss and clay slate/quartzite series. Tectonic history is revealed in two fault directions, a shear-fissure system and indications of recent block-tectonic activity. Climatically, the crest of the east Hindu-Kush forms the diving line between monsoonal and continental areas. The snowline climbs from west to east from 4 900 to 5 300 metres. Glacial activity declines in the same direction. The plant growth of the Wakhan ranges from the desert and semi-desert vegetation of the main valley through steppe like formation to alpine mat vegetation. Apart from on water surfaces, a closed vegetation cover is first encountered at 3 900-4 300 metres (4 500 metres in the Pamirs) on humus-rich northern slopes. Tree growth is almost entirely limited to stream banks and ravines (up to 3 700 metres). Nowhere is it sufficient for forest formation. The upper limit of plant growth lies at about 4 600 metres, for individual flowering species up to 5 100. The inhabitants of the western and central Wakhan are Tadzhik farmers, those of the east are nomadic Kirghiz.